Joint Source and Relay Optimization for Multiuser MIMO Relay Communication Systems - Khandaker, Muhammad; Rong, Yue (IEEE, 2010)
In this paper, we design the source precoding matrices and the relay amplifying matrix of an amplify-andforward multiuser multiple-input multiple-output (MIMO) relay communication system. The minimum mean-squared error (MSE) is taken as the design criterion. We propose an alternating technique to efficiently solve the nonconvex source and relay optimization problem. It is shown that both the optimal source and relay matrices have a beamforming structure. Simulation results demonstrate that the proposed source and relay design algorithms perform much better than the existing techniques in terms of both MSE and bit-error-rate.